Tingkatan Bahasa Jawa dalam Perspektif Metafisika Hans-Georg Gadamer - Tarwiyani, Tri (Jurnal Filsafat "WISDOM", 2011)
Hans Georg Gadamer argued that language is not a system of signs. Language is more than a system of signs. Language, according to Gadamer, does not come from reflective action because language describes subjective reality. It is only a communicated-reality that can be recognized by human. The essence of Gadamerâs metaphysicsis is that language is a world of experience so that between language and the world there is an interrelated relationship. By having language, human has its world because the world is essentially linguistics.The point of Gadamerâs metaphysics is then used to see levelsÂ in the Javanese language. The levels in the Javanese language, namely ngoko, madya, and krama, imply a persons attitude toward his interlocutor who has a different position. This is what Gadamer means, that by analyzing language of a particular community, a social system or class distinction in the community will berecognizable.Keywords: reality, being and language, Javanese language level, class distinction